The Tenebrionidae of the Grand-Duchy of Luxembourg (Coleoptera) - Vitali, Francesco (Zootaxa, 2025)
The first checklist of the Darkling Beetles of the Grand-Duchy of Luxembourg is published based on the literature and the specimens preserved in the National Museum of Natural History of Luxembourg. Thirty-two species are recorder from this country. Cteniopus sulphureus (Linnaeus, 1758); Omophlus lepturoides (Linnaeus, 1758); Isomira murina (Linnaeus, 1758); Nalassus laevioctostriatus (Goeze, 1777); Tribolium confusum Jacquelin du Val, 1861; Melanimon tibiale (Fabricius, 1781); Blaps mortisaga (Linnaeus, 1758); Blaps mucronata Latreille, 1804; Crypticus quisquilius (Linnaeus, 1760); Gnatocerus cornutus (Fabricius, 1798) are reported for the first time.